A New Classification and Clinical Predictivity for Some Naevus Variants. (15th June 2011) - Fabbrocini, G.; Mazzella, C.; Pastore, F.; Monfrecola, A.; Annunziata, M. C.; Mauriello, M. C.; D'Arco, V.; Marasca, C.; De Vita, V.
Abstract : Background . The incidence of cutaneous melanoma is rapidly increasing in Europe. Active research is directed toward the identification of naevi as a risk factor. Objective . The aim of our case-control study was to observe different numbers of moles and different mole typology associations in order to evaluate clinical predictivity and to establish a new classification for some naevus variants. Methods . A case-control study was carried out, enrolling 64 cases affected by melanoma and 183 controls, between October 2009 and February 2011. Each patient was interviewed and subjected to clinical examination. The resulting data were analysed using the statistical elaboration program SPSS 16.0. Results . The association of target naevus with other variants increases the degree of risk (target + small brown Odds Ratio 5.25; confidence interval 1.8–15.4); (target + small brown + small black + large brown odds ratio 5.0; confidence interval 1.1–22.4). Therefore, other variants and/or other variant combinations do not significantly increase risk. Conclusion . People presenting two naevus variants in association with other naevus variants seem to run a major risk. The general nonuniformity of the whole naevus panorama should be carefully considered.